Can economic sanctions be effective? - Maarten Smeets (World Trade Organization (WTO), 2018)
While economic sanctions may be attractive policy tools for governments wanting to express discontent with a country's behaviour, it is arguable if from an economic perspective sanctions can achieve the change that is often envisaged through the punitive measures taken. In fact, the literature does not present conclusive evidence that economic sanctions are an effective policy instrument. Nevertheless the number of sanction episodes is on the rise and have increasingly gained in popularity in recent years. What can explain that? This paper will review how sanctions work from an analytical perspective and the challenges countries encounter in applying sanctions as an effective policy tool. In doing so, it reviews more specifically the sanction episodes against the Russian Federation and Iran and without offering any views on the merits and/or legitimacy of the actions taken by any of the parties. It will be argued that economic sanctions generally inflict economic costs to all countries involved in the sanction episodes, including those taking the sanctions, thus shooting themselves in the foot. The country facing the sanctions is likely to develop trade relations with third parties that are not part of the sanction coalition. It is observed that sanctions are mostly taken in complement of diplomatic and other forms of pressure. The type of sanctions is also evolving, with countries increasingly using 'smart' sanctions, targeting financial transactions, business activities and individuals there were it hurts most and limiting their freedom of movement. From an analytical perspective, it is noted that when various measures are put in place, it is hard to assess the extent to which the economic sanctions per se contribute to the eventual outcomes, hence the question of attribution. It is the combination of various interventions that could eventually make the sanction episodes effective, if at all and not the economic sanctions per se. Despite such shortcomings and lack of evidence of their effectiveness, it can safely be said that they are the preferred option compared to military intervention. At the same time, and regrettably, sanctions do not necessarily prevent armed conflict adding to the economic cost the tragic cost of human life.
Keywords: F13; F51; F52; F53; 330; trade sanctions; conflict; trade theory and policy; national security; international relations